Detection of SalmonellaEnterica with Magnetoelastic Biosensors in Wash Water Containing Clorox and Chlorine Dioxide. (25th October 2017) - Chen, I-Hsuan; Du, Songtao; Liu, Yuzhe; Xi, Jianguo; Lu, Xu; Horikawa, Shin; Wikle, Howard Clyde; Suh, Sang-Jin; Chin, Bryan A.
Abstract : Magnetoelastic (ME) biosensors with phage-displayed oligopeptide probes have been demonstrated to be highly successful in rapid detection of various pathogens, including Salmonella enterica, on the fruit and vegetable surfaces. However, in lieu of testing each produce individually, it is advantageous to detect pathogens in the produce wash water for high-throughput analysis. The sanitizing guidelines of the United States Food and Drug Administration (FDA) suggest adding Clorox and chlorine dioxide to the produce wash water in processing plants to disinfect harmful food-borne pathogens on fruit and vegetable surfaces. Therefore, to determine the efficacy of our ME biosensors in testing for food-borne pathogens in produce wash water, we assessed the stability of our biosensors in the presence of Clorox and chlorine dioxide. Specifically, Enzyme Linked Immunosorbent Assay (ELISA) was used to study the potential effect of Clorox and chlorine dioxide on the S. Typhimurium capturing ability of our phage probe. At concentrations recommended by the FDA for Clorox (100 ppm free chlorine content) and by the United States Environmental Protection Agency for chlorine dioxide (4 ppm), we observed no negative effect of these chemicals on the stability and S. Typhimurium capturing ability of our phage-displayed oligopeptide probe. These data demonstrate the potential efficacy of using our ME biosensors with phage-displayed oligopeptide probes in produce wash waters to determine the presence of food-borne pathogens.